Indonesia’s Membership in BRICS: From Economic Growth Opportunities to Geopolitical Challenges - Putra, Ferdian Ahya Al; Akbar, Muhamad Ali; Sumarman, Muhammad Ilham Aryaputra (Jurnal Hubungan Internasional, 2025)
Indonesia’s accession to BRICS marks a significant milestone in the country’s evolving foreign policy and economic strategy amidst shifting global power configurations. This study examined Indonesia’s membership through the dual lenses of economic opportunity and geopolitical tension, exploring how participation in the BRICS grouping may accelerate economic growth while also posing new strategic dilemmas. By adopting the theoretical framework of cooperation combined with the dual theoretical framework of complex interdependence and middle power diplomacy, the analysis investigated Indonesia’s motivations for joining BRICS, including aspirations to diversify economic partnerships, attract foreign investment, and reduce dependency on Western-led institutions. At the same time, the study highlights potential challenges related to diplomatic alignment, institutional coherence, and the risk of strategic entanglement in rivalries among major powers, particularly China, Russia, and India. Drawing on qualitative policy analysis, official statements, trade data, and geopolitical assessments, the study discovered that while BRICS membership may offer Indonesia enhanced economic bargaining power and access to alternative development finance, it also requires a delicate balancing of its long-held non-aligned stance and ASEAN-centric diplomacy. The study contributes to the literature on South-South cooperation and middle power diplomacy by offering a timely and critical assessment of how emerging economies like Indonesia navigate the evolving architecture of global governance through multilateral platforms like BRICS.